Cognitive Processes on Translation Studies of English Language Learners - Anni Holila Pulungan; Masitowarni Siregar; Rahmad Husein; Nora Ronita Dewi (Britain International for Academic Research (BIAR) Publisher, 2019)
There were many studies discussed on the product of translation. Meanwhile, few researcher lazy to watch the process of translation. This paper, therefore, investigated a study on the processes when a translator performed the translation. The cognitive process played an important role in it. The aims of the study are to describe the think aloud protocols as one of the assessment to explore the translation behaviours or strategies in translation and to analyze cognitive processes that occur in the mind of postgraduate students when they did the translation. This research is also necessary to know the difficulties faced by the students when conducting the process of it. The study that involved fifteen participants, resulted to some difficulties, namely in translating lingual word unit, lingual phrase unit, and lingual clause unit. The overcome strategies were refers to a dictionary, knowledge of the subject (guessing), and the attention of local context and content. It is suggested that, although the think-aloud assessment has limitations, but it is an appropriate instrument for looking into the mental process of a translator.